The Manhattan weather in 1984 and 1985 - L.D. Bark (Kansas Agricultural Experiment Station Research Reports, 1986)
The charts that follow show graphically the daily weather in Manhattan during the last 2 years. Each chart has three smooth curves to represent the average weather conditions at Manhattan based on 70 years of records from the Experiment Station files. The two smooth curves near the top of the charts show the average maximum and minimum temperatures that occur throughout the year. They reach a low point in mid-,January and climb to a peak in mid-July. The smooth curve in the lower part of the chart indicates the average accumulative precipitation during the year. Starting at zero on January 1, it gradually increases throughout the year until it reaches the average annual total precipitation on December 31. This curve climbs quite steeply during mid-year, when considerable rain occurs in Kansas, and less steeply at the beginning and end of the year, when only small amounts of snow or rain are received. The actual temperature and accumulated precipitation totals that occurred throughout 1984 and 1985 are also plotted on these charts so that the "˜weather" can be compared with the climatic averages. Note that on the actual precipitation curve, a horizontal section indicates no rain in that period, and a vertical section means that rain occurred that day.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Weather; Precipitation